Bactérias promotoras de crescimento de plantas associadas à diferentes doses de fertilização nitrogenada na cultura do trigo - Souza, Aline Kelly Pomini de (2016)
Produce wheat competitive and sustainable manner is one of the main challenges of agriculture, because the culture demands a high amount of nitrogen, this element with high cost of obtaining. The objective of this study was to evaluate the ability to promote growth of plant growth promoting bacteria (PGPB) previously isolated from forest areas with different types of soil inoculated by seeds, in wheat plants and the effect of the use of nitrogen fertilizers in the plant-bacteria association. The experiment was been conducted in a randomized block design in a factorial 3 x 7 with four replications. The first factor was composed of 3 doses of nitrogen fertilizer 0; 45 and 90 kg ha-1. The second factor was been formed by the absence of inoculation (control), and inoculation by seeds with the isolates: UFPRPALT2-24, Pseudomonas chlororaphis, UFPRPALM1-131, Ensifer adhaerens, Burkholderia ambifaria and standard strain AbV5 (Azospirillum brasilense), registered in the Ministry of Agriculture. During the experiment were measured the length of plants and chlorophyll content (SPAD). At the flowering stage were measured morphometric and physiological variables (gas exchange and SPAD), and in the end of the crop cycle the production components. Data were been subjected to analysis of variance and regression analysis used for the length of plants and the SPAD index. For the other variables, the averages were been compared by Tukey test at 5% probability of error. For the averages of morphometric analyzes performed at the stage of flowering and maturity was conducted Pearson's correlation and generated groupings of treatments by the methods of Unweighted Pair Group Method with Arithmetic Mean (UPGMA) and Tocher. The morphometric analyzes in the flowering stage was a significant difference in length of plants and number of viable tillers, to the isolated factor. Given the interaction of the factors tested, the significant interaction was observed for: mass of dry matter leaves, mass of dry matter stem, mass of dry matter ears, mass of dry matter of roots and length of ears. In the analysis of gas exchange there was a significant difference for internal CO2 concentration (Ci). Components of production, there was a significant interaction for: ear length, root - aerial part relationship, harvest index, number of grains and grain yield. Pearson's correlation were found 45 correlations, highlighting the relationship of SPAD index, ear length and harvest index, because the chlorophyll content be related to photosynthesis. The groups was observed that the treatments with no inoculation by both UPGMA, and Tocher remained in the same group, separate from treatments that stood out. Given the results exposed, it can being concluded that the bacteria used showed satisfactory results in the development of the wheat crop in combination with nitrogen and compared to Azospirillum brasilense, similar or higher behavior was observed